Land Service Quality in Public Sector: A Bibliometric Analysis - Seran, Gotfridus Goris; Salbiah, Euis; Pratidina, Ginung; Wahyudin, Cecep (Universitas Djuanda, 2025)
Few studies employed bibliometric analysis to examine land service quality in the public sector. Using bibliometric analysis, this research focused on identifying the topics studied, mapping the trend of studies, and presenting future research. This research extracted data from the Google Scholar database through Publish or Perish based on the keyword